WOMEN’S STRUGGLE AGAINST GENDER INEQUALITY POTRAYED IN “MOXIE” MOVIE - Khadijah, St; Nurfadhilah, Auliyanti Sahril; Affandi, Akhmad (Journal of English Literature and Linguistic Studies, 2024)
"Moxie" movie stands out for its focus on youth experiences with gender inequality, shedding light on evolving gender dynamics. This research investigates gender inequality and women's struggles against it as portrayed in the movie "Moxie." The study aims to answer two key questions: 1) What types of gender inequality are depicted in the movie? 2) How do women struggle against gender inequality in the film?. Utilizing "Moxie" as a cultural representation and source of data, the study employed qualitative research methods, data were collected from the movie transcript and supplemented with information from diverse sources. Data analysis techniques by Miles, Huberman, and Saldana were applied, which is data condensation, data display, conclusion drawing/ verification. The findings revealed 37 extracts categorized into five types of gender inequality: marginalization, subordination, stereotyping, violence, and double burden. There are 4 extracts containing cases of marginalization, 2 extracts of subordination, 2 extracts of stereotyping, 6 extracts of violence, and one extract for double burden. There are 21 extracts that relate to women’s struggles, which are  9 extracts about women intellectuals, there are 3 extracts relating to herself, there are 9 extracts relating to women actualizing themselves. Violence emerged as the most prevalent, while double burden was the least frequent. Women's struggles encompassed 21 extracts which are 9 extracts of a woman intellectual, to be herself (3 extracts), and women actualize themselves (9 extracts).